EFEKTIFITAS METODE DARING TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR NEGERI 104214 DELI SERDANG - Desna Fitriana Barus; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2021)
This study aims to determine the effectiveness of the face-to-face method on student learning outcomes SDN 104214 and Knowing the effectiveness of online methods on student learning in SDN 104214 This research is a quasi-experimental research with observation and test data collection techniques. The research subjects were students of class II A and II B SD Negeri 104214 Delitua. The instrument used in this study was a test instrument in the form of a pretest and posttest which was used to determine students' mathematics learning achievement and a non-test instrument in the form of an observation sheet on the implementation of learning. Based on the results of the study, it can be said that the effectiveness of learning with the online method on student learning outcomes in Indonesian class II students at SDN 104214 is still lacking compared to the face-to-face method which can be seen from the average existing post-test scores. Where in the control class the average value of the post-test is 77.00, while the experimental class is 60.50. So it can be concluded that the average student learning outcomes in the control class is 17.50 greater than the experimental class.